Deterministic Automatic Test Pattern Generation for Built-In Self Test System - Mohammed Khalid, Muhammad Nazir (2006)
With a great growing use of electronic products in many aspects of society, it is evident that these products must perform reliably. Their reliability depends on the testing whether or not they have been manufactured properly and behave correctly. To ease testing, digital systems are commonly designed with Built-In Self Test facility. For this reason, development of test pattern for BIST based on combination of Linear Feedback Shift Register (LFSR) and deterministic ATPG (DATPG) approach could provide more solutions, such as reduce testing time, high fault coverage and low area overhead.